The new trigonometrical systems of Aleksandras Dambrauskas - Kalinauskaitė, Nijolė (Lietuvos matematikos rinkinys, 2011)
We review the description of trigonometrical functions via the systems of trigonometric lines as Aleksandras Dambrauskas has done in his book [5].